3.2 Pengamiran Melalui Penggantian


3.2 Pengamiran Melalui Penggantian
 
1. Diberi bahawa ( a x + b ) n d x , n 1.
 
(A) Kaedah Penggantian,
Katakan u=ax+b Oleh itu,  du dx =a           dx= du a

Soalan 1:
Cari ( 3 x + 5 ) 3 d x .

Penyelesaian:
Katakan u=3x+5            du dx =3           dx= du 3 ( 3x+5 ) 3 dx = u 3 du 3    gantikan 3x+5=u dan dx= du 3 = 1 3 u 3 du = 1 3 ( u 4 4 )+c = 1 3 ( ( 3x+5 ) 4 4 )+c    ganti balik  u=3x+5   = ( 3x+5 ) 4 12 +c

(B) Kaedah Rumus
( a x + b ) n = ( a x + b ) n + 1 ( n + 1 ) a + c Oleh itu, ( 3 x + 5 ) 3 d x = ( 3 x + 5 ) 4 4 ( 3 ) + c = ( 3 x + 5 ) 4 12 + c



Soalan 2:
Cari,
(a) 2 7 ( 5 x ) 4 d x (b) 2 3 ( 9 x 2 ) 5 d x

Penyelesaian:
(a) 2 7 ( 5 x ) 4 d x = 2 ( 5 x ) 3 7 ( 3 ) ( 1 ) + c = 2 21 ( 5 x ) 3 + c

(b) 2 3 ( 9 x 2 ) 5 d x = 2 ( 9 x 2 ) 5 3 d x = 2 ( 9 x 2 ) 4 3 ( 4 ) ( 9 ) + c = 2 108 ( 9 x 2 ) 4 + c = 1 54 ( 9 x 2 ) 4 + c


Leave a Comment